Z-DNA/RNA Binding Protein 1 Senses Mitochondrial DNA to Induce Receptor-Interacting Protein Kinase-3/Mixed Lineage Kinase Domain-Like-Driven Necroptosis in Developmental Sevoflurane Neurotoxicity. (15th December 2022) - Wang, Wen-Yuan; Yi, Wan-Qing; Liu, Yu-Si; Hu, Qi-Yun; Qian, Shao-Jie; Liu, Jin-Tao; Mao, Hui; Cai, Fang; Yang, Hui-Ling
Graphical abstract: Highlights: Sevoflurane triggers neuronal cell death and LDH release in a time-dependent fashion. Knockdown of RIPK3, but not RIPK1, abolished MLKL mediated neuronal necroptosis. Sevoflurane exposure causes mitochondrial DNA (mtDNA) release into the cytosol. ZBP1 senses cytosolic mtDNA and consequently activates RIPK3/MLKL signaling. RIPK3 inhibitor GSK'872 attenuates sevoflurane-induced spatial and emotional deficits. Abstract: Developmental sevoflurane exposure leads to widespread neuronal cell death known as sevoflurane-induced neurotoxicity (SIN). Receptor-interacting protein kinase-3 (RIPK3) and mixed lineage kinase domain-like (MLKL)-driven necroptosis plays an important role in cell fate. Previous research has shown that inhibition of RIPK1 activity alone did not attenuate SIN. Since RIPK3/MLKL signaling could also be activated by Z-DNA/RNA binding protein 1 (ZBP1), the present study was designed to investigate whether ZBP1-mediated and RIPK3/MLKL-driven necroptosis is involved in SIN through in vitro and in vivo experiments. We found that sevoflurane priming triggers neuronal cell death and LDH release in a time-dependent manner. The expression levels of RIPK1, RIPK3, ZBP1 and membrane phosphorylated MLKL were also dramatically enhanced in SIN. Intriguingly, knockdown of RIPK3, but not RIPK1, abolished MLKL-mediated neuronal necroptosis in SIN. Additionally, inhibition of RIPK3-mediated necroptosis with GSK'872, rather than inhibition of apoptosis with zVAD, significantly ameliorated SIN. Further investigation showed that sevoflurane treatment causes mitochondrial DNA (mtDNA) release into the cytosol. Accordingly, ZBP1 senses cytosolic mtDNA and consequently activates RIPK3/MLKL signaling. This conclusion was reinforced by the evidence that knockdown of ZBP1 or depleting mtDNA with ethidium bromide remarkably improved SIN. Finally, the administration of the RIPK3 inhibitor GSK'872 relieved sevoflurane-induced spatial and emotional disorders without influence on locomotor activity. Altogether, these results illustrate that ZBP1 senses cytosolic mtDNA to induce RIPK3/MLKL-driven necroptosis in SIN. Elucidating the role of necroptosis in SIN will provide new insights into understanding the mechanism of anesthetic exposure in the developing brain.